Giant Enhancement of Radiative Recombination in Perovskite Light-Emitting Diodes with Plasmonic Core-Shell Nanoparticles - Mikhail A. Masharin; Alexander S. Berestennikov; Daniele Barettin; Pavel M. Voroshilov; Konstantin S. Ladutenko; Aldo Di Carlo; Sergey V. Makarov (Nanomaterials, 2020)
The integration of nanoparticles (NPs) into functional materials is a powerful tool for the smart engineering of their physical properties. If properly designed and optimized, NPs possess unique optical, electrical, quantum, and other effects that will improve the efficiency of optoelectronic devices. Here, we propose a novel approach for the enhancement of perovskite light-emitting diodes (PeLEDs) based on electronic band structure deformation by core-shell NPs forming a metal-oxide-semiconductor (MOS) structure with an Au core and SiO<semantics>2</semantics> shell located in the perovskite layer. The presence of the MOS interface enables favorable charge distribution in the active layer through the formation of hole transporting channels. For the PeLED design, we consider integration of the core-shell NPs in the realistic numerical model. Using our verified model, we show that, compared with the bare structure, the incorporation of NPs increases the radiative recombination rate of PeLED by several orders of magnitude. It is intended that this study will open new perspectives for further efficiency enhancement of perovskite-based optoelectronic devices with NPs.